PERHITUNGAN HARGA POKOK PRODUKSI (FULL COSTING) SEBAGAI DASAR PENETAPAN HARGA JUAL PADA PABRIK KERIPIK TEMPE IBU NOVI DI KELURAHAN GUNUNG SAMARINDA BARU - Prihanisetyo, Adi (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2025)
Calculation of Cost of Goods Manufactured (COGM) is the most important part needed by company management to determine the selling price of a product. To determine the right selling price, the company must first know the COGM of the product to be sold. The company's production results are influenced by the procurement of raw materials, labor, and factory overhead costs. This research aims to understand how to manage financial data from "Mrs. Novi's tempeh chips factory" in Balikpapan, to understand the COGM calculation used by Mrs. Novi's Small and Medium Enterprise (SME) tempeh chips business if using the Full Costing method, and to analyze the comparison between the COGM calculation used by Mrs. Novi's tempeh chips SME and the COGM calculation using the Full Costing method. This research uses a qualitative approach with field research type. Data was obtained by conducting interviews, observations, and documentation. The data analysis technique used is descriptive analysis, which means analyzing by detailing and explaining the relevance of research data in sentence form. The results of this research show that the COGM and selling price of tempeh chips at Mrs. Novi's tempeh chips SME show different results. When using the Full Costing method, the selling price will increase because the Full Costing method calculates all costs related to the production process. Keywords: Cost of Goods Manufactured, Selling Price, Full Costing Method